Encyclopædia iuridica fennica - Mattila, Heikki E. S. (LexicoNordica, 2007)
In Finland, a major legal encyclopaedia, Encyclopædia Iuridica Fennica (EIF), was compiled in the 1990s. The project was initiated and directed by the most important non-profit jurist association in Finland, Suomalainen Lakimiesyhdistys. EIF consists of seven thematic volumes (in each volume the articles are placed in alphabetical order) with a separate index volume. Besides practical purposes, EIF also has cultural aims: the work codifies the totality of the Finnish legal culture. This is why all longer articles include a historical and comparative survey, and one whole volume is consecrated to legal theory, legal history, legal sociology, etc. The present paper describes the properties of this encyclopaedia and the lessons of its compiling: the aims of the project, the organization of its preparation, its structure, the principles of redaction work and the timetable of the work are dealt with. At the end of the paper, there is a summary where the positive and negative experiences gained are described.